Effects of short-term hydrological processes on benthic macroinvertebrates in salt marshes: A case study in Yangtze Estuary, China. (5th March 2019) - Wu, Fengrun; Tong, Chunfu; Feng, Huan; Gu, Jinghua; Song, Guoxin
Abstract: Understanding the effects of hydrological processes on the benthic macroinvertebrates in salt marshes can provide theoretical basis for species diversity restoration, coastal environment protection, and comprehensive exploitation and utilization of salt marsh ecosystems. In this study, 4 fixed-point sampling sites were set up in the salt marsh of the East Nanhui tidal flat in the Yangtze Estuary for benthic macroinvertebrate survey, hydrological monitoring and sedimentary parameter collection over two short-time scales (semidiurnal and fortnightly cycles). Based on the results of these surveys, we analyzed the effects of hydrological processes on the benthic macroinvertebrates over different timescales. The results showed that benthic macroinvertebrates assemblages varied significantly over the semidiurnal and fortnightly tide periods but not between sites. The number of species and the abundance of the benthic macroinvertebrates during spring tide period were significantly lower than that during neap tide period, although the biomass during both tidal periods were not significantly different. There was no significant variation in the number of species, abundance, and biomass of benthic macroinvertebrates over the semidiurnal tidal scale in general with few exceptions. However, there were significant differences in most of the hydrological and sedimentary parameters between the spring and neap tide periods, as well as between semidiurnal tides in these two periods. Two principal components, the intensity of hydrological processes (PC1) and the physicochemical properties of water and sediment (PC2), were derived from principal component analysis on hydrological factors and sedimentary physicochemical parameters. The results show that PC1 had a significant effect on abundance of benthic macroinvertebrate community; while PC2 had a significant effect on biomass. The best combined environmental factors, which exhibited significant correlations with the characteristics of the benthic macroinvertebrates and also their taxonomic classes, varied across the sampling periods. This study indicates that short-term hydrological processes can not only directly affect the benthic macroinvertebrates, but also indirectly affect the communities by altering sedimentary physicochemical factors. There were significant differences in the effects of the hydrological processes on the benthic macroinvertebrate community over the semidiurnal and fortnightly tidal scales, and it could be inferred that the scale effect still exists in the short-time scale. Highlights: Hydrological processes could not only directly but also indirectly affect benthic macroinvertebrates communities. Short-term hydrological processes could affect the number of species and abundance of the benthic macroinvertebrates. The effects of hydrological processes on benthic macroinvertebrates over short timescales still showed scale effects.